Rectal Cancer and Lateral Lymph Node Staging: Interobserver Agreement and Success in Predicting Locoregional Recurrence - Hüseyin Akkaya; Okan Dilek; Selim Özdemir; Turgay Öztürkçü; Mustafa Gürbüz; Zeynel Abidin Tas; Süleyman Çetinkünar; Bozkurt Gülek (Diagnostics)
Objectives: To evaluate the agreement among radiologists in the evaluation of rectal cancer staging and restaging (after neoadjuvant therapy) and assess whether locoregional recurrence can be predicted with this information. Materials and Methods: Pre-neoadjuvant and after-neoadjuvant therapy magnetic resonance imaging (MRI) examinations of 239 patients diagnosed with locally advanced rectal cancer were retrospectively reviewed by three radiologists. The agreement between the MRI findings (localization of tumor involvement, tumor coverage pattern, external sphincter involvement, mucin content of the mass and lymph node, changes in the peritoneum, MRI T stage, distance between tumor and MRF, submucosal sign, classification of locoregional lymph node, and EMVI) was discussed at the September 2023 meeting of the Society of Abdominal Radiology (SAR) and the interobserver and histopathological findings were examined. The patients were evaluated according to locoregional rectal cancer and lateral lymph node (LLN) staging, and re-staging was performed using MRI images after neoadjuvant treatment. The ability of the locoregional and LLN staging system to predict locoregional recurrence was evaluated. Results: Among the parameters examined, for the MRI T stage and distance between the tumor and the MRF, a moderate agreement (kappa values: 0.61–0.80) was obtained, while for all other parameters, the interobserver agreement was notably high (kappa values 0.81–1.00). LLNs during the restaging with an OR of 2.1 (95% CI = 0.33–4.87, p = 0.004) and a distance between the tumor and the MRF of less than 1 mm with an OR of 2.1 (95% CI = 1.12–3.94, p = 0.023) affected locoregional recurrence. A multivariable Cox regression test revealed that the restaging of lymph nodes among the relevant parameters had an impact on locoregional recurrence, with an OR of 1.6 (95% CI = 0.32–1.82, p = 0.047). With the LLN staging system, an increase in stage was observed in 37 patients (15.5%), and locoregional recurrence was detected in 33 of them (89.2%) (p < 0.001). Conclusions: LLN staging is not only successful in predicting locoregional recurrence among MRI parameters but is also associated with a very high level of interobserver agreement. The presence of positive LLN in the restaging phase is one of the most valuable MRI parameters for poor prognosis.